Word reading skills in autism spectrum disorder: A systematic review - Vale, Ana Paula; Fernandes, Carina; Cardoso, Susana (Frontiers in Psychology, 2022)
A growing body of research suggests that children with autism spectrum disorder (ASD) are at risk of reading and learning difficulties. However, there is mixed evidence on their weaknesses in different reading components, and little is known about how reading skills characterize in ASD. Thereby, the current study aimed to systematically review the research investigating this function in children with ASD. To this purpose, we reviewed 24 studies that compared (1) children with ASD and children with typical development (TD) in word and nonword reading performance, (2) children with ASD and normative data of word and nonword reading tests, and (3) the results obtained by children with ASD in word and nonword reading tests. Most of the comparisons (62%) contrasting the reading performance of children with ASD and children with TD did not find significant differences between groups in both word and nonword reading. However, all the comparisons that reported standardized results showed that children with ASD had scores that fell within population norms. Regarding the third comparison of interest, about 54% of the studies presented data for both word and nonword reading, but only one study tested the difference between them and showed that children with ASD had higher levels of word than of nonword reading. Despite these results, the heterogeneous and small samples do not allow to draw sound conclusions regarding the strategies that children with ASD use to read words. As consequence, the nature of reading difficulties presented by children with ASD are still unknown, requiring future research conducted with larger and well-characterized samples of ASD and TD, using homogeneous specific tasks designed to assess word reading strategies.